Data-driven evolutionary game models for the spread of fairness and cooperation in heterogeneous networks - Li, Jing-Yi; Wu, Wen-Hao; Li, Ze-Zheng; Wang, Wen-Xu; Zhang, Boyu (Frontiers in Psychiatry, 2023)
The unique large-scale cooperation and fairness norms are essential to human society but the emergence of the prosocial behaviors is elusive. The fact that heterogeneous social networks prevail raised a hypothesis that heterogeneous networks facilitate fairness and cooperation. Yet, the hypothesis has not been validated experimentally, and little is known about the evolutionary psychological basis of cooperation and fairness in human networks. Fortunately, researches about oxytocin, a neuropeptide, may provide novel ideas for confirming the hypothesis. Recent oxytocin-modulated network game experiments observed that intranasal administration of oxytocin to a few central individuals significantly increases global fairness and cooperation. Here, based on the experimental phenomena and data, we show a joint effect of social preference and network heterogeneity on promoting prosocial behaviors through building evolutionary game models. In network ultimatum game and Prisoner’s dilemma game with punishment, inequality aversion can lead to the spread of costly punishment on selfish and unfair behaviors. This effect is initiated by oxytocin, then amplified via influential nodes, and finally promotes global cooperation and fairness. In contrast, in the network trust game, oxytocin increases trust and altruism but these effects are confined locally. These results uncover general oxytocin-initiated mechanisms underpinning fairness and cooperation in human networks.